From Lyric to Meaning: Self-Healing in Tulus’ “Diri” Through Barthes’ Semiotics - Maulidita, Nayla; Jati, Rocky Prasetyo (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
This study analyzed the lyrics of "Diri" by Tulus using Roland Barthes’ semiotic approach to explore how the song constructs and conveys the concept of self-healing. Released in 2022 during a period of emotional transition for Indonesian youth following the COVID-19 pandemic, the song presented themes of self-acceptance, emotional honesty, and psychological resilience. The research applied Barthes’ three-tier model of meaning—denotation, connotation, and myth to uncover how symbolic messages in the lyrics represent both individual emotional experiences and broader cultural narratives. The lyrical content was examined through qualitative content analysis, with each selected verse interpreted for its literal, emotional, and ideological significance. The findings revealed that "Diri" serves as more than personal reflection; it also functions as a cultural artifact that reinforces emerging values of emotional independence and mental well-being in urban Indonesian society. Through verses that encourage forgiveness, self-talk, and emotional boundaries, the song communicates ideals that resonate with contemporary youth. However, it also reflects the tension between personal responsibility and collective support in the process of healing. This study demonstrated the relevance of semiotic analysis in interpreting psychological discourse within popular music. It contributed to expanding the application of Barthes’ theory beyond Western contexts and offered insights into how music can shape and reflect emotional culture. The results may serve as a foundation for future research in cultural studies, media psychology, and the role of art in mental health awareness.